Intensification of Biodiesel Production by Optimizing Process Parameters from Waste Cooking Oil through Response Surface Methodology. Issue 1 (1st December 2022) - Mohanraj, J.; Kannan, G. R.; Elango, M.
Abstract: This study focused catalytic transesterification process for the production of biodiesel from restaurant based waste cooking oil. Fifteen pre-designed experiments are used to explore the significance of three reaction parameters with three different levels such as methanol to oil ratio, catalyst concentration and agitation speed as well as their combined effect on biodiesel production. Box-Behnken experimental design based on Response Surface methodology (RSM) is utilized for optimizing the process parameters A quadratic model was developed to estimate biodiesel yield, and the R 2 value was determined to be 0.99, indicating that the model is accurate. The result showed optimized process parameters for maximum biodiesel yield as methanol:oil molar ratio of 12.97:1, NaOH concentration of 0.1834 wt% and at the agitation speed of 1088 rpm. The obtained results reveal that the yield of 98.45% and the experimental yield of 97.80% respectively which shows the deviation of 0.7%.